2013
DOI: 10.1212/wnl.0b013e3182887957
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of seropositive NMO spectrum disorder and MS brain lesion distribution

Abstract: Objective: Neuromyelitis optica and its spectrum disorder (NMOSD) can present similarly to relapsingremitting multiple sclerosis (RRMS). Using a quantitative lesion mapping approach, this research aimed to identify differences in MRI brain lesion distribution between aquaporin-4 antibody-positive NMOSD and RRMS, and to test their diagnostic potential.Methods: Clinical brain MRI sequences for 44 patients with aquaporin-4 antibody-positive NMOSD and 50 patients with RRMS were examined for the distribution and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
169
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(192 citation statements)
references
References 24 publications
11
169
2
10
Order By: Relevance
“…12 Although nonspecific small dots and patches of hyperintensity in subcortical and deep white matter on T2-weighted or fluid-attenuated inversion recovery sequences are the most common findings in NMOSD, certain lesions have a location or appearance characteristic for NMOSD. 6,7,[11][12][13][14][15] Before the discovery of anti-AQP4 antibody, brain MRI abnormalities were reported in only 13% to 46% of patients with NMO. 1,8,16 However, when excluding the brain MRI criteria, the incidence of brain MRI abnormalities increased to 50% to 85% using the revised 2006 NMO diagnostic criteria 3,11,13,17,e1-e3 and to 51% to 89% in seropositive patients with NMOSD.…”
Section: Brain Mri Findings In Nmosdmentioning
confidence: 99%
See 4 more Smart Citations
“…12 Although nonspecific small dots and patches of hyperintensity in subcortical and deep white matter on T2-weighted or fluid-attenuated inversion recovery sequences are the most common findings in NMOSD, certain lesions have a location or appearance characteristic for NMOSD. 6,7,[11][12][13][14][15] Before the discovery of anti-AQP4 antibody, brain MRI abnormalities were reported in only 13% to 46% of patients with NMO. 1,8,16 However, when excluding the brain MRI criteria, the incidence of brain MRI abnormalities increased to 50% to 85% using the revised 2006 NMO diagnostic criteria 3,11,13,17,e1-e3 and to 51% to 89% in seropositive patients with NMOSD.…”
Section: Brain Mri Findings In Nmosdmentioning
confidence: 99%
“…However, it is now known that MS-like lesions may appear in 10% to 12.5% of cases, 11,e3 and 5% to 42% of patients with NMO fulfill the Barkhof criteria. 6,14,15,47 A recent report showed that 13% and 9% of patients with NMOSD, respectively, met Barkhof and the European Magnetic Imaging in MS diagnostic criteria for MS on brain MRI at onset. 7 Lesion probability maps have not found statistically significant lesion locations in patients positive for anti-AQP4 antibody over those with MS. 6 However, distinguishing features were identified on MS brain MRI that were sensitive and specific, such as the presence of a lateral ventricle and inferior temporal lobe lesion, Dawson fingers, or an S-shaped U-fiber lesion, to classify the patient as MS.…”
Section: Comparing the Imaging Of Nmosd Withmentioning
confidence: 99%
See 3 more Smart Citations